2014
DOI: 10.1039/c4cy00445k
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective phenol production from benzene on a platinum-loaded tungsten oxide photocatalyst with water and molecular oxygen: selective oxidation of water by holes for generating hydroxyl radical as the predominant source of the hydroxyl group

Abstract: Particles of tungsten oxide loaded with nanoparticulate platinum (Pt/WO 3 ) photocatalytically produced phenol from benzene with high selectivity (e.g., 74% at 69% of benzene conversion) in water containing molecular O 2 ; the selectivity for phenol were much higher than those on conventional titanium oxide 10 (TiO 2 ) photocatalysts (both the unmodified and Pt-loaded) that generated CO 2 as a main product. Results confirmed that photoexcited electrons in the Pt/WO 3 photocatalysts mainly generated H 2 O 2 fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 49 publications
1
65
0
Order By: Relevance
“…( Fig. 4) Small particles in a size range of a few or several nanometers that were not observed in nonplatinized samples are seen in all of the images, and any form of BWO could be platinized by photocatalytic deposition using hexachloroplatinic acid and methanol as a precursor of Pt and an electron donor, respectively [28]. Immediately after the commencement of photoirradiation, the color of the suspensions changed from light pale yellow to dark grey or black, indicating the formation of metallic Pt particles, but little evolution of hydrogen was detected in either the one-step or two-step deposition method, as is usually observed for deposition of Pt on titania particles.…”
Section: Pt-photodeposited Bwo Samplesmentioning
confidence: 95%
“…( Fig. 4) Small particles in a size range of a few or several nanometers that were not observed in nonplatinized samples are seen in all of the images, and any form of BWO could be platinized by photocatalytic deposition using hexachloroplatinic acid and methanol as a precursor of Pt and an electron donor, respectively [28]. Immediately after the commencement of photoirradiation, the color of the suspensions changed from light pale yellow to dark grey or black, indicating the formation of metallic Pt particles, but little evolution of hydrogen was detected in either the one-step or two-step deposition method, as is usually observed for deposition of Pt on titania particles.…”
Section: Pt-photodeposited Bwo Samplesmentioning
confidence: 95%
“…Unlike TiO 2 -noble metal heterojunction, wherein noble metal induces singleelectron based oxygen reduction process, metal islands at the surface of WO 3 acts as co-catalyst to trigger multielectron based oxygen reduction pathways. The latter is more useful for the partial oxidation of organic compounds leading to selective synthesis (like benzene hydroxylation to phenol, partial oxidation of cyclcohexane to cyclohexanol and cyclohexanone), while former always results in complete mineralization [107,108]. The photoaction spectrum analysis concluded that the photoexcited electron reacts with oxygen to initiate multielectron reduction, rather being trapped to generate W 5+ upon metal loading [109].…”
Section: Noble Metal Deposited Womentioning
confidence: 96%
“…It was hypothesized that the high selectivity is due to the presence of the platinum co-catalyst, which favors the twoelectron reduction of O 2 . 152 This results in the formation of mainly H 2 O 2 and thus avoids the formation of stronger oxidizing radical species, such as˙O 2 − and˙HO 2 . The formed H 2 O 2 can be rapidly decomposed in water and oxygen, consequently, having an insignificant effect on the oxidation pathway (Scheme 55).…”
Section: View Article Onlinementioning
confidence: 99%